Alternative fuels guidebook : properties, storage, dispensing, and vehicle facility modifications - Bechtold, Richard L., 1952- (Society of Automotive Engineers, 1997)
This book presents the fundamentals needed to understand the physical and chemical properties of alternative fuels, and how they impact refueling system design and the modification of existing garages for safety. It covers a wide range of fuels including alcohols, gases, and vegetable oils.
Keywords: Spark ignition engines -- Alternative fuels.; elektronické knihy; electronic books